Observation and modeling of an unusual spatiotemporal pattern in bioacoustic chorusing - D’Spain, Gerald L.; Rovner, Galina L.; Batchelor, Heidi; Rimington, Dennis B. (Frontiers in Remote Sensing, 2024)
This paper describes an unusual underwater biological chorus recorded in the Southern California Bight and presents a numerical model that replicates aspects of the chorus. During one experiment, the evolution in directionality of the chorusing region over time is suggestive of "The Wave" performed by fans periodically standing and sitting in sports stadia around the world; here, the region of chorusing periodically propagated upcoast over 20 km at nearly 1.5 km/sec. The chorus occurs predominantly at night in spring and summer, mostly in shallow coastal waters. It increases the underwater sound levels within chorusing regions by 20 to 30 dB in the 50 Hz to 1 kHz band. The chorus is composed of: 1) a "sunset chorus", 20 to 30 min of continuous roar around sunset with received spectral levels up to 100 dB re 1 uPa^2/Hz, 2) a "sunrise chorus" of lower level than at sunset, and 3) an all-night-long cycling chorus comprised of 15-to-20 sec periods of higher spectral levels each followed by a 10-to-20 sec lull where levels drop by 4 to 10 dB. This alternating pattern repeats every 30-40 sec throughout the night. The modeling approach is based on the physics of excitable media. A cellular automaton models the two-dimensional spatial grid occupied by the calling animals (units), with each unit being either in the "resting", "excitable", or "active (calling)" state at each time step. Transition from resting to excitable and from active to resting occurs after a fixed period of time in the present state, whereas the probability of transitioning from excitable to active is determined both by the elapsed time since becoming excitable and by the sound level received by the unit, creating a non-linear acoustics-based coupling between units. With appropriate inputs, simulations with the model can replicate the cycling nature of the night-long chorus levels, the continuous din of the sunset chorus, and (once properly initialized) the periodic upcoast evolution of the chorusing region. Noise from a transiting ship causes the simulated spatiotemporal characteristics of the chorus to change appreciably, in ways similar to changes observed during the experiment.